2010
DOI: 10.1364/oe.18.012599
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and delayed images
through an image resonator

Abstract: We performed optical image propagation experiments in an image resonator consisting of a Fabry-Perot resonator in reflection geometry. Two-dimensional images encoded on optical pulses of 32ns were stored, and either advanced, -6.0ns, or delayed, 10.9ns, using the dispersion relation relevant to the image resonator, in the under- or over- coupling condition, respectively. The overall images are propagated through the resonator clearly, while the diffraction effects were analyzed both in real-space and in k-spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The present Fourier analysis not only reproduces the reported experimental observations [15,16] but also predicts new aspects of the time evolution of image propagation through the cavity; the propagated image profiles are time dependent. To demonstrate the new aspect of the time evolution, we performed time-and space-resolved image propagation experiments.…”
Section: Experimental Demonstrationsupporting
confidence: 84%
See 4 more Smart Citations
“…The present Fourier analysis not only reproduces the reported experimental observations [15,16] but also predicts new aspects of the time evolution of image propagation through the cavity; the propagated image profiles are time dependent. To demonstrate the new aspect of the time evolution, we performed time-and space-resolved image propagation experiments.…”
Section: Experimental Demonstrationsupporting
confidence: 84%
“…Figures 3(c)-3(e) are the reflected images obtained from the single resonator using a continuous wave input beam for the under, critical, and over coupling conditions, respectively. Several characteristic aspects of the 2D image propagation that was obtained experimentally [15,16] were also reproduced in the Fourier analysis. We observed that the edge region of the image was enhanced for the under coupling condition (Figure 3(c)).…”
Section: Stationary Image Propagation Through Single and Coupled Resomentioning
confidence: 92%
See 3 more Smart Citations